2018
DOI: 10.3390/w10070842
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Bacterial Community Diversity Formed in Different Groundwater Field Corresponding to Electron Donors and Acceptors Distributions at a Petroleum-Contaminated Site

Abstract: Abstract:The benefits of an electron-transfer mechanism for petroleum biodegrading have been widely acknowledged, but few have studied the spatial pattern of microbial community diversity in groundwater fields, and few discuss the bacterial community's diversity in relation to electron donors-acceptors distribution, which is largely determined by groundwater flow. Eleven samples in different groundwater fields are collected at a petroleum-contaminated site, and the microbial communities are investigated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…However, as in our study, the relationship between contaminates load (uranium) and functional genes richness was insignificant. In another study however, diversity in groundwater polluted with hydrocarbons in China, was lower than the downstream groundwater, likely due to the dominance of degrading bacteria [48].…”
Section: Pollution Extent Affects Community Diversitymentioning
confidence: 83%
“…However, as in our study, the relationship between contaminates load (uranium) and functional genes richness was insignificant. In another study however, diversity in groundwater polluted with hydrocarbons in China, was lower than the downstream groundwater, likely due to the dominance of degrading bacteria [48].…”
Section: Pollution Extent Affects Community Diversitymentioning
confidence: 83%
“…The number of OTUs unique to RIC_S (713) was much higher than those in QSC_S and NFC_S (309 and 292). Other researchers have demonstrated that soil bacterial community diversity can gradually decrease with significant removal of soil organic C by leaching, dissolution, and aerobic transformation (Ning et al., 2018). This could explain the diversity differences between the vadose zone communities, but not the similar diversity in the oscillated zone communities or that the highest diversity in the saturated zone was exhibited by RIC.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies considered anthropogenic sources, with Beretta et al [7] and Haluska et al [6] addressing the industrial additive and known carcinogen hexavalent chromium, Plymale et al [8] focusing on the toxic salt ferrocyanide, Haluska et al [6] measuring the organic contaminants 1,4-dioxane and hexahydro-1,3,5-trinitro-s-triazine (RDX), Prieto-Amparán et al [9] studying sewage effluent, and Wells et al [10] tracking the fertilizer-derived anion nitrate. As a particular subset of anthropogenic contaminants, two studies discuss emerging contaminants, particularly related to hydrocarbon resources, as Hu et al [11] study oil shale development, while Ning et al [12] focus on petroleum contamination.…”
Section: Groundwater Contaminationmentioning
confidence: 99%
“…In parallel, Hu et al [11] discuss the potential impacts from emerging contaminants related to oil shale development. Three studies explore the central role of biology in groundwater remediation, reflecting our new understanding of subsurface processes through the interdisciplinary lens of biogeochemistry: Ning et al [12] study the spatial pattern of bacterial communities at a petroleum-contaminated site; Plymale et al [8] study bacterial communities at a nuclear waste-contaminated site; and Moradi et al [14] contribute a model describing thermally-enhanced bioremediation. Taken together, these studies demonstrate that our ability to remediate groundwater depends on knowing the contaminants, understanding the fluid mechanics, and interpreting processes in the context of hydrology, geochemistry, and microbiology.…”
Section: Subsurface Processesmentioning
confidence: 99%